Effects of HDV infection and pegylated interferon α treatment on the natural killer cell compartment in chronically infected individuals. Issue 3 (10th April 2014) - Lunemann, Sebastian; Malone, David F G; Grabowski, Jan; Port, Kerstin; Béziat, Vivien; Bremer, Birgit; Malmberg, Karl-Johan; Manns, Michael P; Sandberg, Johan K; Cornberg, Markus; Ljunggren, Hans-Gustaf; Wedemeyer, Heiner; et al.
Abstract : Objective: Although hepatitis delta is considered an immune-mediated disease, adaptive immune responses to hepatitis delta virus (HDV) are hardly detectable. Thus, the role of other immune responses, including those mediated by natural killer (NK) cells, must be considered in HDV pathogenesis and in treatments with immune-stimulating agents such as interferon (IFN)α. However, the phenotype and function of NK cells in chronic HDV infection, or in HDV-infected individuals undergoing IFNα treatment, have not been extensively studied. Design: We performed an extensive analysis of NK cells in chronically HDV-infected patients before and during treatment with IFNα, and compared the results with those for patients with HBV mono-infection as well as healthy controls. Results: In untreated HDV-infected patients, a higher than normal frequency of NK cells was observed in peripheral blood with unaltered phenotypic NK cell differentiation status. In contrast, long-term IFNα treatment of HDV-infected patients caused a significant change in NK cell differentiation status, with selective loss of terminally differentiated NK cells and, in parallel, a relative enrichment in immature NK cell subsets. Treatment was associated with marked functional impairment of the NK cells, which was independent of the changes in NK cell differentiation status. Furthermore, treatment polarised NK cell IFN signalling from STAT4 towards STAT1 dependency. Strikingly, a high frequency of CD56 dim NK cells at baseline was positively associated with IFNα treatment outcome in the patients. Conclusions: We describe in detail how HDV infection, and IFNα treatment of this infection, affects the NK cell compartment and what consequences this has for the functional capacity of NK cells.